Identifying Negative Interactions in Protein-Protein Interaction Network Using Weak Edge-edge Domination Set. (2016) - Izudheen, Sminu; Mathew, Sheena
Abstract: Link prediction has recently attracted the attention of many researchers as an effective technique to understand the associations between proteins. But most of the work in this area was concentrated on predicting existence of links in future. Very few works has explored the prediction of links that might disappear in future. Also, links predicted by these methods may contain high levels of wrong interactions. In this paper, we propose a method to optimize the negative link predicted in protein network through Weak Edge-Edge Domination (WEED) set. We have tested our model using different standard prediction methods and the results obtained assert that our method can be used as an effective method to reduce false positive rate of negative links predicted in protein network.